2008
DOI: 10.1128/aac.00533-08
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intergenotypic Chimeric Replicons To Determine the Broad-Spectrum Antiviral Activities of Hepatitis C Virus Polymerase Inhibitors

Abstract: To address the need for broad-spectrum antiviral activity characterization of hepatitis C virus (HCV) polymerase inhibitors, we created a panel of intergenotypic chimeric replicons containing nonstructural (NS) protein NS5B sequences from genotype 2b (GT2b), GT3a, GT4a, GT5a, and GT6a HCV isolates. Viral RNA extracted from non-GT1 HCV patient plasma was subjected to reverse transcription. The NS5B region was amplified by nested PCR and introduced into the corresponding region of the GT1b (Con-1) subgenomic rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 50 publications
3
53
1
Order By: Relevance
“…especially rare and that the replication complex is typically encoded on the same genomic strand that it will replicate and transcribe (2). It is also interesting that when replication complexes are exchanged between different genotypes, the replication efficiency is substantially reduced (15). The pseudodiploidy of the HIV genome certainly increases the likelihood of recombination occurring due to the ability of the virus to package two RNA templates (17), while the secondary RNA structure in the HCV genome may limit the production of viable hybrid HCVs (59,68).…”
Section: Figmentioning
confidence: 99%
“…especially rare and that the replication complex is typically encoded on the same genomic strand that it will replicate and transcribe (2). It is also interesting that when replication complexes are exchanged between different genotypes, the replication efficiency is substantially reduced (15). The pseudodiploidy of the HIV genome certainly increases the likelihood of recombination occurring due to the ability of the virus to package two RNA templates (17), while the secondary RNA structure in the HCV genome may limit the production of viable hybrid HCVs (59,68).…”
Section: Figmentioning
confidence: 99%
“…Each of these NNIs targets four different binding pockets of the HCV polymerase, thumb-1 NNI-1 (10), thumb-2 NNI-2 (29,48), palm-1 NNI-3 (9), and palm-2 NNI-4 (19), respectively. Historically, the screen for novel NS5B inhibitors was limited to representatives of genotype 1b only (3,28) because the tools to target other genotypes were not yet available (16,38,40). Further assessment of these analogs, using enzyme isolates and intergenotypic chimeric replicons derived from clinical iso-lates, revealed that the genotypic coverage of the NNI-1 and -4 analogs extends beyond genotype 1, unlike the NNI-2 and -3 derivatives that typically inhibit genotype 1 only (16,38).…”
mentioning
confidence: 99%
“…Further assessment of these analogs, using enzyme isolates and intergenotypic chimeric replicons derived from clinical iso-lates, revealed that the genotypic coverage of the NNI-1 and -4 analogs extends beyond genotype 1, unlike the NNI-2 and -3 derivatives that typically inhibit genotype 1 only (16,38). An additional drawback stems from the lower genetic barrier of the NNI-2 and -3 analogs in genotype 1 (25) and the reduced susceptibility in subtype 1a of the NNI-3 series (7,16,34,38,43). This effect was mostly attributed to the Y415F polymorphism observed in the NNI-3 binding site in subtype 1a (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated the utility of chimeric replicons for broadspectrum activity determination of HCV inhibitors. Herlihy et al created a panel of intergenotypic chimeric replicons harboring NS5B sequences from different genotypes (2b, 3a, 4a, 5a, 6a) (Herlihy et al, 2008). Stable cell lines were generated with replicationcompetent chimeras in order to evaluate the antiviral activity of HCV nonnucleoside polymerase inhibitors (NNIs) that target different regions of the protein.…”
Section: Hcv Targeting By New Chemical Entitiesmentioning
confidence: 99%